2012
DOI: 10.3928/01477447-20121023-18
|View full text |Cite
|
Sign up to set email alerts
|

Locking Versus Nonlocking Palmar Plate Fixation of Distal Radius Fractures

Abstract: This study compared functional and radiological outcomes after treatment of extension-type distal radius fractures with conventional titanium nonlocking T-plates or titanium 1.5-mm locking plates. A total of 60 patients were included and followed for 4 to 7 years after receiving nonlocking T-plates (group A; n=30) or locking plates (group B; n=30) with and without dorsal bone grafting. Bone grafting was significantly more often performed in the nonlocking group to increase dorsal fracture fixation and stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…Jones et al reported that in their retrospective study conducted in a sample of 221 patients with fractures of the distal radius, the scapholunate instabilities evaluated by means of posterior-anterior and lateral projections appeared as unusual either in the setting of acute wrist fracture or in association with the progression of hidden injuries of ligaments -even despite early rehabilitation (13). This is, why some authors do not immobilize fractured wrists at all (14); others fi x them for 1-2, 3, 4 weeks or longer (13,(15)(16)(17). Some studies have yielded better short-term results as to the function and movement range of the wrist in patients who had their wrists immobilized for 1 or 3 weeks as compared with those who had their wrists fi xed for 6 weeks (18).…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al reported that in their retrospective study conducted in a sample of 221 patients with fractures of the distal radius, the scapholunate instabilities evaluated by means of posterior-anterior and lateral projections appeared as unusual either in the setting of acute wrist fracture or in association with the progression of hidden injuries of ligaments -even despite early rehabilitation (13). This is, why some authors do not immobilize fractured wrists at all (14); others fi x them for 1-2, 3, 4 weeks or longer (13,(15)(16)(17). Some studies have yielded better short-term results as to the function and movement range of the wrist in patients who had their wrists immobilized for 1 or 3 weeks as compared with those who had their wrists fi xed for 6 weeks (18).…”
Section: Discussionmentioning
confidence: 99%
“…Of course in other hospitals the postoperative treatment of distal radius fractures is handled differently [ 9 , 14 , 16 ], sometimes even with no immobilization at all [ 15 ]. With increasing age of our future patients and thus reduced bone quality the confidence into postoperative stability might decrease and therefore postoperative immobilization to safeguard the operative result might be used more often in future even by those not doing it presently.…”
Section: Discussionmentioning
confidence: 99%
“…While surgical treatment has meanwhile become the gold standard [ 10 , 11 ] and depending on the type of fracture is usually performed from volar [ 12 , 13 ] under utilization of locking plates [ 14 ], to date hardly any studies have been conducted with regard to postoperative therapy and especially the effect of immobilization during the postoperative period. Some of the authors do not mention postoperative immobilization at all, some seem to completely dispense postoperative immobilization [ 15 ] and others perform postoperative immobilization in a circumferential cast or a splint for 2 weeks [ 16 , 17 ], three weeks [ 9 ] or even up to four weeks [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plate fixation is increasingly being applied in the treatment of comminuted distal radius fractures, and short-term follow-up demonstrates satisfactory results (Huang et al, 2005). Moreover, the post-healing functional score after the application of palmar T-shaped locking plates is superior to those with other methods such as non-locking plate fixation (Osti et al, 2012), dorsal plate fixation (Rausch et al, 2013), and percutaneous Kirschner wire fixation (Grewal et al, 2011). Nevertheless, although the use of a palmar T-shaped locking plate combined with a dorsal plate (Ring et al, 2005) or the technique of combining volar plating with locked radial column plating or K-wire fixation (Tang et al, 2010) can achieve satisfactory results, they incur greater trauma and more late complications.…”
Section: Introductionmentioning
confidence: 99%